2013
DOI: 10.1097/cej.0b013e32835b6a60
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and dietary folate intake and the risk of breast cancer

Abstract: Owing to its interaction with alcohol, folate has been suggested to be a potential factor for many types of cancer. The impact of these factors on the risk of breast cancer among Asian populations has not been fully examined, however, particularly with respect to receptor status. We carried out a case-control study in premenopausal and postmenopausal Japanese women, including 1754 breast cancer patients and 3508 noncancer controls. We determined the association between self-reported alcohol drinking, dietary f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 40 publications
4
17
0
Order By: Relevance
“…Although increased folate intake may be good for a population deficient in this nutrient, increased intake in women with already-sufficient levels of folate may provide no further benefit or actually be harmful. Several previous studies did not report a significant association with breast cancer risk (Vaĭner et al, 2010;Islam et al, 2013;, which is in line with our results. The results indicated that folate intake could not play a protective role in breast cancer for women who had a nutritional deficiency.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Although increased folate intake may be good for a population deficient in this nutrient, increased intake in women with already-sufficient levels of folate may provide no further benefit or actually be harmful. Several previous studies did not report a significant association with breast cancer risk (Vaĭner et al, 2010;Islam et al, 2013;, which is in line with our results. The results indicated that folate intake could not play a protective role in breast cancer for women who had a nutritional deficiency.…”
Section: Discussionsupporting
confidence: 83%
“…Low dietary folate intake has been associated with risk of various cancers, such as colorectal cancer, pancreatic cancer, prostate cancer and gastric cancer (Bassett et al, 2013;Lin et al, 2013;Collin, 2013;Gao et al, 2013). Recently, several studies reported a protective effect of folate intake on breast cancer risk Yang et al, 2013;Islam et al, 2013). However, evidence from two recent studies have indicated an inverse association (Ericson et al, 2007;Maruti et al, 2009a), and some other studies have shown that the reduced risk only exists in certain populations, such as women with high levels of alcohol intake or premenopausal Chinese women (Levi et al, 2001;Shrubsole et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that high intake of folate is beneficial to women who are deficient in nutrient gain. Several previous studies have reported inconsistent results for folate intake and breast cancer risk (Ma et al, 2009;Wu et al, 2012;Tavani et al, 2012;Islam et al, 2013;Qin et al, 2013; Yang et al, 2013). In our study, we reported that folate intake does not play a protective role in breast cancer risk in Chinese population.…”
Section: Discussionsupporting
confidence: 42%
“…Although increased folate intake may be good for population deficient in this nutrient, increased intake in women with already-sufficient levels of folate may provide no further benefit or actually harmful. Previous several studies did not report a significant association with breast cancer risk (Vaĭner et al, 2010;Islam et al, 2013), which is in line with our results. The results indicated folate intake could not play a protective role in breast cancer for women who already have deficient in nutrition.…”
Section: Discussionsupporting
confidence: 83%